THE METHODICAL APPROACH TO THE ESTIMATION OF THE IMPORTANCE OF TAXES IN FORMING OF INCOMES OF BUDGETARY SYSTEM OF THE RUSSIAN FEDERATION ON THE EXAMPLE OF THE BELGOROD REGION - Valentina F. Tarasova; Tatiana V. Saprykina; Marina L. Shitikova (Статистика и экономика)
Article is devoted questions of formation of tax incomes of budgetary system of the Russian Federation. Approaches of a regional tax policy are proved by granting of tax privileges. The system of factors allowing quantitatively to estimate value of tax payments in formation own and aggregate prots of the budget is offered; approbation on an example of the budget of the Belgorod region is spent.